(untitled) (Research, Society and Development, 2023)
The hospital pharmacy is a sector that encompasses several functions, among them the management of orthotics, prostheses and special materials (OPME). These materials have a high cost and represent a significant portion of the financial expenses of a hospital unit. Within this context, the pharmaceutical professional is essential to guarantee the safety and quality of the health care process, from the receipt of materials in the hospital unit to the correct dispensing of these specialized products. The objective of this work is to carry out a systematic review of the literature on the subject: The role of the pharmacist in the hospital management of orthoses, prostheses and special materials, using the Scielo (Scientific Electronic Library Online), LILACS (Latin American Literature and Caribe em Ciências da Saúde), LA Referência (Federated Network of Institutional Repositories of Scientific Publications), MEDLINE (Medical Literature Analysis and Retrievel System Online), from 2016 to 2021. highlighted the importance and versatility of the pharmacist in the management of OPME, both in the production chain of materials, and in the stages of pharmacovigilance and techno-surveillance.